CROSS-CULTURAL COMPARISON OF UGC COMMUNICATION FOR SINO-ITALIAN VISUAL INTANGIBLE CULTURAL HERITAGE ON INSTAGRAM: A CASE STUDY OF VENETIAN MASKS AND PEKING OPERA FACIAL MASKS - Wang, Chuyao; Adzharuddin, Nor Azura; Sharipudin, Mohamad-Noor Salehhuddin; Dong, Qingchen; Guo, Zhiyao (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study investigates how visual intangible cultural heritage (ICH) is communicated across cultures via social media by comparing Instagram posts featuring Venetian carnival masks and Peking Opera facial masks. Drawing on UNESCO’s definition of ICH and theories of intercultural communication, we conducted a qualitative content analysis of public Instagram images and captions tagged with relevant hashtags from 2020–2024. The sample comprised 120 posts for each mask type, purposively selected to capture a range of users and contexts. Using inductive thematic analysis, we identified how creators frame heritage and identity for global audiences. Venetian mask posts predominantly emphasize craft tradition, festive tourism, and aesthetic design, often highlighting handmade artistry and historical context. In contrast, Peking Opera mask posts focus on symbolic roles, cultural education, and national heritage, frequently referencing character types and explaining color meanings. Both sets of posts use Instagram’s visual affordances and hashtags (#VeniceCarnival, #PekingOpera, etc.) to engage global viewers, but they reflect distinct cultural contexts: Italian users foreground artistic interpretation and spectacle, whereas Chinese users foreground performance symbolism and cultural continuity. These findings suggest that Instagram serves as a platform for bridging intangible heritage across cultures, but creators’ cultural perspectives shape the representation. The study contributes a nuanced understanding of digital ICH transmission, demonstrating that social media can support intercultural dialogue by making heritage practices visible and understandable beyond their origin communities. Methodologically, this purely qualitative analysis of public Instagram data provides transparent coding procedures and researcher reflexivity. We conclude that engaging younger global audiences through platforms like Instagram can help sustain ICH by connecting community traditions to wider audiences.